Anion···π Interactions and Metastability: Structural Transformations in a Silver–Pyrazine Network. Issue 19 (23rd May 2017) - Gee, William J.; Robertson, Karen; Skelton, Jonathan M.
Abstract : Structural evidence of anion··· π interactions influencing single‐crystal‐to‐single‐crystal (SCSC) transformations is demonstrated herein with a metastable silver–pyrazine system. A cascade of SCSC transformations driven by changes to anion··· π stabilisation sees two metastable species convert to a ground‐state form. This constitutes one of the most dramatic chemical effects yet attributed to anion··· π interactions. Metastable networks [Ag(µ‐NO2 )(pyz)] (1, 2 ) are composed of dimerised (1 ) and delaminated (2 ) AgNO2 /pyrazine, which convert to the ground‐state [Ag(κ 2 ‐NO2 )(pyz)] form3 with 3D connectivity. The metastable phases show responsiveness to solvent vapour and temperature. This work shows how anion··· π interactions influence solid‐state structure with support from computational modelling and highlights how metastable materials may harness anion··· π interactions to deliver large structural and property changes. Abstract : Humble pie: Anion··· π interactions are shown here to play a key role in facilitating a cascade of single‐crystal‐to‐single‐crystal transformations. These new silver–pyrazine metastable materials exhibit responsiveness towards temperature and specific solvent vapours, and detailed X‐ray diffraction and computational investigations provide insights into a plausible solid‐state conversion mechanism.